The role of cis-regulatory elements in Plasmodium falciparum transcriptional regulation - Lim, Eng How (2015)
Malaria remains to be a global problem and has caused approximately 700,000 deaths per year. Plasmodium falciparum (P. falciparum) is a eukaryotic apicomplexan parasite and is one of the causative agents of malaria. The transcriptome of P. falciparum during the intraerythrocytic developmental cycle (IDC) is characterized by a highly regulated cascade of transcripts where 60-80% of the 5500 genes in the parasite genome are expressed at least once. However, mechanisms of transcriptional control are not well characterized in P. falciparum. In particular, there is a lack of functional cis-regulatory DNA motifs described in P. falciparum. We have utilized an algorithm to predict DNA motifs on co-regulated genes and tested their functionality by transfection assays. Interestingly, we have found an overrepresentation of motifs which repress transcription. We have also found that the repressive effects of several of motifs were stage specific and regulate transcription of groups of genes. Hence, this leads us to propose repression of transcription as a form of transcriptional regulation in P. falciparum.